Correlation of wind waves and sea level variations on the coast of the seasonally ice-covered Gulf of Finland - M. M. Johansson; J.-V. Björkqvist; J. Särkkä; U. Leijala; K. K. Kahma (Natural Hazards and Earth System Sciences, 2022)
Both sea level variations and wind-generated waves affect coastal flooding risks. The correlation of these two phenomena complicates the estimates of their joint effect on the exceedance levels for the continuous water mass. In the northern Baltic Sea the seasonal occurrence of sea ice further influences the situation. We analysed this correlation with 28 years (1992–2019) of sea level data, and 4 years (2016–2019) of wave buoy measurements from a coastal location outside the City of Helsinki, Gulf of Finland in the Baltic Sea. The wave observations were complemented by 28 years of simulations with a parametric wave model. The sea levels and significant wave heights at this location show the strongest positive correlation ( τ =0.5 ) for southwesterly winds, while for northeasterly winds the correlation is negative ( −0.3 ). The results were qualitatively similar when only the open water period was considered, or when the ice season was included either with zero wave heights or hypothetical no-ice wave heights. We calculated the observed probability distribution of the sum of the sea level and the highest individual wave crest from the simultaneous time series. Compared to this, a probability distribution of the sum calculated by assuming that the two variables are independent underestimates the exceedance frequencies of high total water levels. We tested nine different copulas for their ability to account for the mutual dependence between the two variables.